PAUL RUDOLPH’S DESIGN PRINCIPLES ON HIGH-RISE OFFICE BUILDINGS IN INDONESIA CASE STUDY: WISMA DHARMALA SAKTI JAKARTA AND WISMA DHARMALA SAKTI SURABAYA - Sukada (Jurnal Riset Arsitektur, 2018)
Abstract- Many of high-rise office buildings in Indonesia applies efficiency and effectivity of building form, cost, and time for construction as a number one priority. As a result, high-rise office buildings appears with a minimum-articulated form, and show the dominance by using glass materials as a facade. However, there are also high-rise office buildings that have an articulated form and its facades that are not dominated by glass, although they appear in small numbers. Wisma Dharmala Sakti Jakarta and Wisma Dharmala Sakti Surabaya are one of them. Moreover, both buildings were designed by foreign architect, Paul Rudolph. Based on the potentials of both buildings, this research focused on Paul Rudolph’s principles in designing high-rise office buildings in Wisma Dharmala Sakti Jakarta and Wisma Dharmala Sakti SurabayaLooking at the phenomena of high-rise office buildings in Indonesia as described earlier, this small number and the articulated form of high-rise office buildings designed by Paul Rudolph in Indonesia are interesting to be understood even more. The main purpose of this research is to reveal the relationship between Paul Rudolph’s design principles with buildings, which are Wisma Dharmala Sakti Jakarta and Wisma Dharmala Sakti Surabaya. Using an interpretative method in a qualitative research, this research utilized theories that helps understanding of an office building, theories that related to Paul Rudolph’s background and common thought about architecture, and also Paul Rudolph’s theory about determinants of architectural form as a literature study. Building’s Anatomy Theory is used as a surgical tool to disect the study cases, which happens to be Wisma Dharmala Sakti Jakarta and Wisma Dharmala Sakti Surabaya.Result of this research are six points of Paul Rudolph’s principles in designing high-rise office building which are: repetition, space, scale, rotation, light, and context. Implementation of Paul Rudolph’s design principles in both study cases can be seen in the dominance of rotation and repetition of building elements. The application of these two principles can fulfill all the three aspects of Paul Rudolph’s design ideal, which are form, context, and cycle.Benefit of this research is to enrich architectural vocabulary about design principles of a high-rise office buildings in Indonesia for the concerned educational institution, as a consideration and input to architects and the stakeholders to be more sensitive and critical in designing high-rise buildings in Indonesia, as a reference and study case about design principles of a high-rise office buildings for students, academics, architects, and the public with the focus of study concerned, and enrich the knowledge about Paul Rudolph’s design principles especially in designing high-rise office buildings in Indonesia for researcher. Keywords: Paul Rudolph, Design Principles, Office, Wisma Dharmala Sakti Jakarta, Wisma Dharmala Sakti Surabaya.